2003
DOI: 10.1023/b:appa.0000010381.24903.1c
|View full text |Cite
|
Sign up to set email alerts
|

Amblyomma aureolatum and Ixodes auritulus (Acari: Ixodidae) on birds in southern Brazil, with notes on their ecology

Abstract: Between January 1999 and December 2000, 876 bird specimens were captured in three different ecological environments from the Reinhard Maack Park, Curitiba, State of Paraná, southern Brazil. A total of 142 birds (16.2%) were infested with Amblyomma aureolatum (Pallas 1772) (N=699) and/or Ixodes auritulus Neumann, 1904 (N=18) ticks. Questing A. aureolatum nymphs (N=2) and adults (N=5) were also collected from the soil and the vegetation. None of the I. auritulus were collected off-host. We collected only immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 12 publications
2
21
1
5
Order By: Relevance
“…Birds of the genus Turdus were previously reported to be important for the life cycle of several tick species, once they live in low forest stratum and are commonly found on the ground (ROJAS et al, 1999;ARZUA et al, 2003;VENZAL et al, 2005). In this study, we observed this bird genus parasitized by Amblyomma larvae, and nymphs of A. calcaratum and A. longirostre, with high prevalence and mean intensity.…”
Section: Discussionmentioning
confidence: 50%
“…Birds of the genus Turdus were previously reported to be important for the life cycle of several tick species, once they live in low forest stratum and are commonly found on the ground (ROJAS et al, 1999;ARZUA et al, 2003;VENZAL et al, 2005). In this study, we observed this bird genus parasitized by Amblyomma larvae, and nymphs of A. calcaratum and A. longirostre, with high prevalence and mean intensity.…”
Section: Discussionmentioning
confidence: 50%
“…Among 61 tick species reported in Brazil (Dantas-Torres et al 2009), 18 species from five genera have been reported parasitizing wild birds in different biomes other than the Amazon rainforest (Aragão 1911(Aragão , 1936Arzua et al 2003Arzua et al , 2005Arzua and BarrosBattesti 1999;Barros-Battesti et al 2003;Evans et al 2000;Labruna et al 2007a;Ogrzewalska et al 2008Ogrzewalska et al , 2009Szabó et al 2008;Terrassini et al 2006). The Amazon biome is the largest rainforest of the world, with most of its extension (4,900,000 km 2 ) in northern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…The few available records of natural hosts for sub-adults of A. aureolatum have included mostly a few bird and rodent species 9,10,11,12 . Meanwhile, it has been reported that A. aureolatum adult ticks feed mainly on dogs in rural areas close to remnants of rainforest 11,13,14 .…”
Section: Introductionmentioning
confidence: 99%